Antibacterial, pro-angiogenic and pro-osteointegrative zein-bioactive glass/copper based coatings for implantable stainless steel aimed at bone healing - Ramos Rivera, Laura; Cochis, Andrea; Biser, Sarah; Canciani, Elena; Ferraris, Sara; Rimondini, Lia; Boccaccini, Aldo R. (Bioactive Materials, 2021)
Stainless steel implants are suitable candidates for bone replacement due to their cytocompatibility and mechanical resistance, but they suffer from lack of bioactivity and are prone to bacterial infections. Accordingly, to overcome those limitations, in this study we developed by electrophoretic deposition (EPD), an innovative surface coating made of (i) zein, a natural fibroblast-friendly polymer, (ii) bioactive glass, a pro-osteogenic inorganic material and (iii) copper containing bioactive glass, an antibacterial and pro-angiogenic material. FESEM images confirmed that porous, uniform and free of cracks coatings were obtained by EPD; moreover, coatings were resistant to mechanical stress as demonstrated by the tape test, resulting in a 4B classification of adhesion to the substrate. The coatings were cytocompatible as indicated by metabolism evaluation of human fibroblasts, endothelial cells and mature or progenitor osteoblasts cultivated in direct contact with the specimens. They also maintained pro-osteogenic properties towards undifferentiated progenitor cells that expressed osteogenic genes after 15 days of direct cultivation. Copper conferred antibacterial properties as biofilm formation of the joint pathogens Staphylococcus aureus, Staphylococcus epidermidis and Escherichia coli was significantly reduced in comparison with copper-free coatings (p < 0.05). Moreover, this anti-infective activity resulted as targeted towards bacteria while the cells viability was preserved when cells and bacteria were cultivated in the same environment by a co-culture assay. Finally, copper ability to recruit blood vessels and to inhibit bacterial infection was confirmed in vivo where the growth of S. aureus biofilm was inhibited and the formation of new (<50 μm diameter spread) blood vessels was observed.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Antibacterial; Bioactive glass; Bone; Copper; Zein

Bioactive and Antibacterial Coatings Based on Zein/Bioactive Glass Composites by Electrophoretic Deposition - Meyer, Nima; Ramos Rivera, Laura; Ellis, Tim; Qi, Jiahui; Ryan, Mary P.; Boccaccini, Aldo R. (Coatings, 2018)

Bioactive Glass Containing Coatings by Electrophoretic Deposition: Development and Applications - Heise, Svenja; Ramos Rivera, Laura; Boccaccini, Aldo R. (Biomedical, Therapeutic and Clinical Applications of Bioactive Glasses, 2018)

Development and characterization of new bioactive and antibacterial coatings for biomedical applications using electric field assisted processing - Ramos Rivera, Laura (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2019)

Electrophoretic deposition of anisotropic α-Fe2O3/PVP/chitosan nanocomposites for biomedical applications - Ramos Rivera, Laura; Distaso, Monica; Peukert, Wolfgang; Boccaccini, Aldo R. (Materials Letters, 2017)
Electrophoretic deposition (EPD) has been used to fabricate composite coatings based on anisotropic hematite particles ( extgreeka-Fe2O3) comprising residual poly-N-vinyl-pyrrolidone (PVP) and chitosan (CHT) on stainless steel substrates. The experimental conditions towards homogeneous surface, non-delamination and good distribution of extgreeka-Fe2O3/PVP particles are described. The coatings were characterized by SEM, XRD and TGA. A molecular interaction between PVP adsorbed on the surface of the particles and CHT is identified.
EAM Import::2019-03-14
Keywords: Electrophoretic deposition; Hierarchical structures; Porous layers; PVP/Chitosan interaction

Formation of Zein/Bioactive Glass Layers Using Electrophoretic Deposition Technique - Ramos Rivera, Laura; Dippel, Jannik; Boccaccini, Aldo R. (ECS Transactions, 2018)
Coatings of zein and zein/bioactive glass composites were produced on 316L stainless steel using anodic electrophoretic deposition (EPD). Zein and 45S5 bioactive glass were dispersed in a binary water/ethanol solution. The effects of the zein and bioactive glass concentrations as well as different water/ethanol ratios on the coating characteristics were investigated. Also, the influence of applied voltage and deposition time were analyzed. Prior to EPD, the zeta potential of zein, bioactive glass and zein/bioactive glass suspensions were measured as a function of the pH. The coatings were investigated by optical microscopy, scanning electron microscopy and atomic force microscopy. Coatings with pure zein are homogeneous when using an electrical field strength below or equal to 0.05 V/m. Higher voltages led to a discoloration of the solution which could result from a conformational change of zein. The co-deposition of zein/bioactive glass is very sensitive to the applied voltage and the concentration of zein. High concentrations of zein (10 g/L) increase the viscosity of the solution and reduce the electrophoretic mobility of the bioactive glass. Equal concentration of zein and bioactive glass at a pH of 7.5 with a low electric field strength were found to be the optimum condition

Poly(ε-caprolactone)/poly(glycerol sebacate) electrospun scaffolds for cardiac tissue engineering using benign solvents - Vogt, Lena; Ramos Rivera, Laura; Liverani, Liliana; Piegat, Agnieszka; El Fray, Miroslawa; Boccaccini, Aldo R. (Materials Science and Engineering C, 2019)
Electrospun fibers based on combinations of poly(ε-caprolactone) (PCL) and poly(glycerol sebacate) (PGS) have been studied for applications in cardiac tissue engineering. The aim of the present study is to demonstrate the fabrication of PCL and PGS prepolymer or mildly crosslinked PGS by electrospinning using less toxic solvents, like acetic acid, as opposed to conventional solvents such as chloroform or dichloromethane. The morphological and physiochemical properties and degradation susceptibility of the fiber mats were determined. A cell study using ST2 cells was performed to assess cytocompatibility. Neat PCL and PCL/PGS blends showed defect-free microstructures, whereby the average fiber diameter increased with the addition of PGS (0.8 ± 0.3 μm and 1.3 ± 0.7 μm, respectively). The mechanical properties were tested at 23 °C and 37 °C and showed higher values compared to native human myocardium. Degradation studies revealed a fast PGS degradation but the mildly cross-linked PGS resulted in acidification of the degradation medium. The biocompatibility was significantly increased when the samples were disinfected in 70% v/v ethanol in comparison to ultra-violet light disinfection. PCL/PGS fibers fabricated with acetic acid proved to be potentially suitable for application in cardiac tissue engineering based on their mechanical properties and biodegradability.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Acetic acid; Cardiac patch; Cardiac tissue engineering; Electrospinning; Poly(glycerol sebacate); Poly(ε-caprolactone)

Zein-based composites in biomedical applications - Demir, Merve; Ramos Rivera, Laura; Silva, Raquel; Nazhat, Showan Najdat; Boccaccini, Aldo R. (Journal of Biomedical Materials Research Part A, 2017)
Considerable research efforts have been devoted to zein-based biomaterials for tissue engineering and other biomedical applications over the past decade. The attention given to zein-based polymers is primarily attributed to their biocompatibility and biodegradability. However, due to the relatively low mechanical properties of these polymers, numerous inorganic compounds (e.g., hydroxyapatite, calcium phosphate, bioactive glasses, natural clays) have been considered in combination with zein to create composite materials in an attempt to enhance zein mechanical properties. Inorganic phases also positively impact on the hydrophilic properties of zein matrices inducing a suitable environment for cell attachment, spreading, and proliferation. This review covers available literature on zein and zein-based composite materials, with focus on the combination of zein with commonly used inorganic fillers for tissue engineering and drug delivery applications. An overview of the most recent advances in fabrication techniques for zein-based composites is presented and key applications areas and future developments in the field are highlighted
Keywords: zein; composi tes; scaffolds; bone tissue engin eering

Zein-Based Electrospun Fibers Containing Bioactive Glass with Antibacterial Capabilities - Mariotti, Camilla E.; Ramos Rivera, Laura; Conti, Bice; Boccaccini, Aldo R. (Macromolecular Bioscience, 2020)
Zein, a natural protein from corn, has important applications in food and pharmaceutical industries due the fact that it is biodegradable and biocompatible. However, due its relatively low mechanical properties and water solubility, many inorganic compounds (e.g., bioactive glasses [BGs]) have been used in combination with zein to obtain composite materials with improved mechanical properties. Such inorganic additions provide further biological functionality to zein. In this work, fiber mats of zein with incorporation of BG and copper doped BG particles are successfully obtained by electrospinning. At first the electrospinnability of the blends is assessed, then the morphological and chemical characterization of the mats is done. Degradation study in cell culture medium (Dubelcco’s modified Eagle’s medium) reveals a sufficient strength of the fibers, which in turn is necessary for in vitro cellular studies. Cell culture studies using MG-63 and C2C12 cells show promising results, demonstrating increased cell proliferation and growth for fiber mats containing both types of BGs. Also, evaluation with Staphylococcus aureus and Escherichia coli bacteria confirms the antibacterial activity of the scaffolds containing copper. The presence of Cu thus imparts antibacterial properties without influencing cell behavior. The developed electrospun fibers represent a novel scaffold system for tissue engineering applications.
CRIS-Team Scopus Importer:2020-06-05
Keywords: antibacterial effect; bioactive glass; copper; electrospinning; zein